A Rare Case of Pedunculated Fibrolipoma in the Gluteal Region: Diagnostic and Surgical Journey - Priyadarshee, Piyoosh; Ashwinkumar A, Ashwinkumar A; G. Murugan, G. Murugan; Baskar A, Baskar A (Journal of Neonatal Surgery, 2025)
Pedunculated fibrolipomas are an uncommon variant of benign lipomatous tumors characterized by a mixture of adipose and fibrous tissue. We report the case of a 39-year-old male who presented with an asymptomatic, soft, and mobile mass in the left infragluteal fold, which had gradually enlarged over 8 months to approximately 10 cm in length and 5 cm in diameter. Radiological assessments—including ultrasound, computed tomography, and magnetic resonance imaging—revealed a well-circumscribed, lipomatous lesion with a vascular stalk, suggestive of a benign process. The lesion was successfully excised via a meticulous surgical procedure, and histopathological analysis confirmed the diagnosis of fibrolipoma. This case highlights the significance of a comprehensive diagnostic approach combining clinical evaluation and multimodal imaging to distinguish rare fibrolipomas from other soft-tissue masses, thereby guiding effective surgical management